PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PERSONAL BRANDING CALON LEGISLATIF(CALEG) PROVINSI BALI 2019 - Wardani, Sri Yulia; Pramana, Gede Indra; Mahaswari Jayanthi Mertha, Anak Agung Sagung Mirah (Jurnal Nawala Politika; 2021: Jurnal Ilmu Politik 2021, 2021)
Today is very important to pay attention to utilizing technology, especially social media in building a brand. Personal branding can grow and develop in anyone, one of them who has used social media as a medium for personal branding and won the most votes in the 2019 Bali Provincial legislative election is Agung Suyoga. This research discusses how back stage and front stage play the role of Agung Suyoga through Instagram @RelawanAgungSuyoga. Purpose of this study is to determine the use of Instagram as personal branding. Research method used is qualitative approach. Data was collected using interview and documentation. Results show that Personal branding advice requires perceptions effectively, controlling and influencing how others perceive and think about an individual, and necessary to be yourself and be positive in any case. Good personal branding cannot be built in a relatively short time, but takes consistency, intention and action to build it. Key Words : Personal Branding,Instagram,Dramaturgy,Legislative Candidates